KAJIAN HADITS TENTANG PENTINGNYA SALAM SEBAGAI SARANA PENDIDIKAN ANAK AGAR BERBAKTI KEPADA ORANG TUA - Burhanuddin Ridlwan; Laily Masruroh; Syamsuddin (EL-Islam, 2019)
The hadith about the importance of greetings as a means of education and habituation of children to be devoted to parents, which is contained in the book of Imam al-Bukhari "Al-Adab Al-Mufrad", interesting to be studied and re-examined both in terms of sanad and matannya. The focus of the problem in this study are: First: the position of the hadith and about the importance of greetings as a means of education for children to serve the parents. Second: shaheed or shahwah for matan hadith about the importance of greetings as a means of children's education so that they arefilial to their parents. Third: fiqhul hadith from the hadith about the importance of greetings as a means of children's education so that they are filial to parents. The research method used in this study is the study of library (Library Research) or literary studies. The results of this study, First: That the rawi named Said al-bin abi hilal according to the majority of hadith scholars and jarh wa ta'dil is tsiqah (reliable), not dlo'if (ikhtilath) as alleged by al-Albani and ibnu khazm , among these are reinforced by the opinion of Ibn Hajar, Abu Hatim, Ibn Hibban, and Abul Barakat MuhammadMuhammad Ibn Ahmad known as Ibni Kayal who all stated Tsiqah. Second: That in the study of Matan hadith about the importance of greetings as a means of children's education to be devoted to people old there are four shaheed hadiths, and the four shahid hadiths can be shahwah for the main hadith. Third: Discussion of the importance of greetings as a means of children's education so that filial piety can be concluded that familiarizing greetings between children and parents can foster mutual love and love.